An overview of primary health care in geriatric and need of care intervention (A comparative study of Czech Republic, Sweden, and Canada) - Rehana Sindho, Kabooro (Magyar Gerontológia, 2023)
This researche is aiming to evaluate the care interventions and approaches for the ageing population in different countries and their perspective of geriatric care. Quality assurance and workforce development the monitoring supervision and evaluation of care progression is very demanding for the sustainable delivery of care and frequent trainings and education of healthcare professionals develop quality geriatric care.